High-Speed Boundary-Layer Stability and Transition - Lysenko, V.I. (Engineering Transactions, 1993)
In this paper peculiarities of the laminar hypersonic (Mach numbers 4-16) boundary layer stability and its transition to the turbulent one are studied experimentally and numerically at different facilities. The influence of various factors on the boudary-layer stability and the transition is considered.